Eurasian Whooper Swan Cygnus cygnus migration with particular reference to birds wintering in southern Sweden - Mathiasson, Sven (Wildfowl, 2013)
The Whooper Swan, a breeder of the Palearctic taiga lakes, spends the winter in both Atlantic and Pacific areas, as well as in lakes and streams of central Asia. The population is split into fractions by migration dividers, also smaller subpopulations display specific migration characters. Factors influencing the migratory behaviour are discussed, partly based on sightings of neck-collared birds, partly based on field observations.